Cover Image. (11th February 2020) - Okonogi, Noriyuki; Wakatsuki, Masaru; Kato, Shingo; Murata, Hiroto; Kiyohara, Hiroki; Karasawa, Kumiko; Ohno, Tatsuya; Tsuji, Hiroshi; Nakano, Takashi; Shozu, Makio; ,
Abstract : The cover image is based on the Original Research Significance of concurrent use of weekly cisplatin in carbon‐ion radiotherapy for locally advanced adenocarcinoma of the uterine cervix: A propensity score‐matched analysis by Noriyuki Okonogi et al., https://doi.org/10.1002/cam4.2784 . Cover image © Noriyuki Okonogi, QST hospital Images.